Evaluating the Risks and Benefits of Genetically Modified Agricultural Products in the Global Marketplace - Bessoff, Noah (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: none available.